P05.04 Phase 2 open-label study of maintenance treatment with ibrutinib following first line methotrexate-based immuno-chemotherapy in elderly patients with primary CNS lymphoma (PCNSL) - Bairey, O (Neuro Oncol, 2019)
BACKGROUND: Patients older than 60 years account for up to 70% of all PCNSL cases. Elderly PCNSL patients have median overall survival (OS) under 2 years and progression free survival (PFS) ranging between 6–16 months. Older patients have multiple comorbidities associated with low tolerability to high-dose (HD) chemotherapy. As maintenance treatment proved to prolong PFS and\or OS in several hematological malignancies we sought to investigate whether Ibrutinib maintenance may benefit elderly PCNSL patients. Ibrutinib was selected for maintenance since it has an impressive tolerability and activity in a range of systemic B-cell lymphomas. MATERIAL AND METHODS: Single arm, open label, non-randomized study aiming to accrue 30 newly diagnosed PCNSL patients aged 60–85 years who received HD-methotrexate-based first line chemotherapy and have a documented response which is either partial (PR) or complete response (CR). The primary end-point is one and 2-year PFS and maintenance ibrutinib dose is 560mg/day. All patients undergo pre-maintenance neurocognitive evaluation which is repeated every 6 months. RESULTS: Of the 14 patients screened for the study 2 were excluded due to relapse while on screening. 12 patients have been enrolled with a median age of 74 (61–80) years. The median interval between diagnosis of PCNSL and start of ibrutinib maintenance is 7.6 (5.6–11.5) months. Currently, the median PFS is 22.5 (12–31.5) months. The adverse effects are largely grade 1/2 with rare grade 3/4 events. One patient discontinued treatment due to skin rash at 4.5 months and she is still alive after 24 months. Two patients relapsed while on maintenance after 4 and 15 months of treatment. 3 patients with PR at enrolment improved to CR/CRu during maintenance. No invasive fungal infections have been observed. CONCLUSION: Ibrutinib maintenance is feasible and well tolerated in newly diagnosed elderly PCNSL patients after first-line HD-Methotrexate based treatment. The toxicity is mild to moderate. Enrollment is ongoing and updated outcomes will be presented at the meeting.